Gearing towards efficient problem solving: Exploring the determinants that influence success - RODIL, MARY SHEENALYN (Journal of Interdisciplinary Studies in Education, 2024)
Enhancing students’ skills as competent problem solvers is one of the primary educational challenges. For students to succeed, it is essential to determine the elements that best encourage and develop problem-solving abilities. With the help of SEM’s strong statistical framework, a model that shows how self-efficacy, grit, utility value, help seeking behavior and executive control interact and contribute to problem solving efficiency was developed. The path analysis, combined with students’ explanation, provided strong support for the framework, and among the determinants examined in the study, utility value and executive control, were observed to exert a significant influence on college students’ problem solving proficiency. The implication of these findings is that enhancement of students’ higher-order cognitive processes involved in planning, monitoring and regulating cognition and their perceptions of task usefulness should be the main goals of interventions designed to increase problem solving abilities.